2014
DOI: 10.5935/1676-2444.20140013
|View full text |Cite
|
Sign up to set email alerts
|

Methemoglobin measure in adult patients with sickle-cell anemia: influence of hydroxyurea therapy

Abstract: Introduction: Hemoglobin S (HbS) is unstable hemoglobin that easily oxidizes, causing methemoglobin (MetHb) increased production in patients with sickle-cell anemia (SCA). Objectives: To determine MetHb levels and the influence of hydroxyurea (HU) therapy on this marker in patients with SCA. Materials and methods: Blood samples from 53 patients with SCA at the steady-state, with and without HU therapy, and 30 healthy individuals were collected to evaluate MetHb levels. The MetHb measurement was performed by sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
1
1
0
Order By: Relevance
“…HU therapy was also observed to significantly reduce HbS levels, which is consistent with results by Shome et al who also found an association between HU use and significantly reduced HbS levels in SCA patients [ 38 ]. We also detected significantly higher HbF levels in SCA-HU + patients compared to controls, which confirms results in previous studies regarding the efficacy of HU in inducing HbF synthesis [ 3 , 34 , 39 , 40 ].…”
Section: Discussionsupporting
confidence: 90%
“…HU therapy was also observed to significantly reduce HbS levels, which is consistent with results by Shome et al who also found an association between HU use and significantly reduced HbS levels in SCA patients [ 38 ]. We also detected significantly higher HbF levels in SCA-HU + patients compared to controls, which confirms results in previous studies regarding the efficacy of HU in inducing HbF synthesis [ 3 , 34 , 39 , 40 ].…”
Section: Discussionsupporting
confidence: 90%
“…NADPH oxidases are not the only intracellular sources of ROS. Normal cellular metabolism produces hydrogen peroxide (H 2 O 2 ) (examples: peroxisomal oxidases that convert O 2 to H 2 O 2 ; the cytochrome P450 system [ 1 ]; xanthine oxidase reaction and certain stressful or pathological conditions produce superoxide, and indirectly H 2 O 2 [examples: aged mitochondria through “leakage” of single electrons in complexes I and III [ 2 ]; production of methemoglobin in certain mutant hemoglobins like HbS [ 3 ]]. Additionally, deleterious ROS are also produced by biogenic and non-biogenic environmental attacks from outside [for instance as a secondary consequence of ionizing radiation, IR], leading to oxidative stress).…”
Section: Introductionmentioning
confidence: 99%